2014
DOI: 10.1111/bjh.13138
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, severity and correlates of fatigue in newly diagnosed patients with myelodysplastic syndromes

Abstract: SummaryThe primary objective of this study was to investigate factors associated with fatigue severity in newly diagnosed patients with higher-risk myelodysplastic syndromes (MDS). The secondary objectives were to assess symptom prevalence and to examine the relationships between fatigue, quality of life (QoL) and overall symptom burden in these patients. The analyses were conducted in 280 higher-risk MDS patients. Pre-treatment patient-reported fatigue was evaluated with the Functional Assessment of Chronic I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 33 publications
9
61
0
Order By: Relevance
“…[6][7][8] Indeed, patients with MDS suffer from a wide variety of symptoms including fatigue, anxiety, insomnia, and dyspnea. 9 It is essential to understand such patient-reported outcomes for their own value, and not just for their potential contribution to disease risk. Although an Internet-based survey of MDS patients' QOL has been published, 10 no MDS-specific QOL measure has been widely adopted for clinical or research use.…”
Section: Prospective International Validation Of the Quality Of Life mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Indeed, patients with MDS suffer from a wide variety of symptoms including fatigue, anxiety, insomnia, and dyspnea. 9 It is essential to understand such patient-reported outcomes for their own value, and not just for their potential contribution to disease risk. Although an Internet-based survey of MDS patients' QOL has been published, 10 no MDS-specific QOL measure has been widely adopted for clinical or research use.…”
Section: Prospective International Validation Of the Quality Of Life mentioning
confidence: 99%
“…Although an Internet-based survey of MDS patients' QOL has been published, 10 no MDS-specific QOL measure has been widely adopted for clinical or research use. Researchers aiming to assess the impact of MDS and its treatments 9,[11][12][13][14][15][16][17][18] on QOL have most often used generic measures such as the Short-Form Health Survey (SF-36), 19 or cancer-specific scales such as the European Organization for Research and Treatment of Cancer's QLQ-C30 20 and the Functional Assessment of Cancer Therapy-Anemia (FACT-An). 21 While these measures are useful, they are not specific enough to contain all of the elements important to MDS-related QOL, and may contain several less relevant items.…”
Section: Prospective International Validation Of the Quality Of Life mentioning
confidence: 99%
“…Therefore, it is not unlikely that it is associated with other adverse events. Recently studies have reported that fatigue is associated with other common adverse events, such as CIPN, and greater levels of fatigue were associated with greater symptom severity [11,18,19]. Additional analysis of data of a previous study [12] showed significantly (p50.0001) more fatigue, measured by the total score of the fatigue assessment scale, in patients with the 10% highest CIPN scores (N ¼ 141, mean ¼ 25.38, SD ¼ 8.43) compared to those with lower CIPN scores (N ¼ 1348, mean ¼ 19.41, SD ¼ 5.84).…”
mentioning
confidence: 99%
“…The rationale for this study was the fact that fatigue by far is one of the most compromising symptoms in MDS [4]. In a recent study by Efficace and colleagues, more than 90% of patients experienced fatigue and 30% reported to have moderate to severe fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…http Among others, fatigue is also the most prevalent and disabling patient reported outcome (PRO) as reported by more than 90% of patients [4]. Other symptoms like dyspnea, insomnia and pain affect more than half of the patients.…”
Section: Introductionmentioning
confidence: 99%